Thermal degradation and lifetime estimation of poly(ether imide)/carbon fiber composites - Batista, Natassia L.; Costa, Michelle Leali [UNESP]; Iha, Koshun; Botelho, Edson C. [UNESP] (Sage Publications Ltd, 2015)
The thermal decomposition behavior of poly(ether imide) (PEI)/carbon fiber composites used in aeronautical field was studied using thermogravimetric analysis in an inert atmosphere, at several heating rates between 2 and 10 degrees C min(-1). The activation energies (E-a) were determined by Flynn-Wall-Ozawa (FWO) and Kissinger methods, and the preexponential factor (A) was calculated by the FWO method. The obtained data were used in order to predict the thermal lifetime of the material under the established temperature range and 5% mass loss criterion. Overall, the results represented PEI's good thermal stability. Furthermore, it was concluded that the material can be safely applied for aeronautical use.
Keywords: PEI; Carbon fiber composites; Thermogravimetric analysis; Kinetics; Lifetime prediction